Magmatic and rifting-related features of the Lomonosov Ridge, and relationships to the continent–ocean transition zone in the Amundsen Basin, Arctic Ocean - Funck, Thomas; Shimeld, John; Salisbury, Matthew H (Geophysical journal international, 2022)
The continental Lomonosov Ridge spans across the Arctic Ocean and was the subject of a geophysical study in 2016 with two seismic reflection lines crossing the ridge in proximity to the North Pole, one of which continues across the continent–ocean transition zone into the Amundsen Basin. One seismic station and 15 sonobuoys were deployed along these two lines to record seismic wide-angle reflections and refractions for development of a crustal-scale velocity model. Its viability is checked using gravity data from the experiment which are also used to interpolate crustal structure in areas with poor seismic constraints. On the line extending into the Amundsen Basin, continental crust composed of two layers with velocities of 6.0 and 6.5 km s–1 is encountered beneath the Lomonosov Ridge where the Moho depth is 21 km based on gravity modelling. The crust is overlain by a 1-km-thick layer with velocities of 4.7 km s–1 coinciding with a zone of positive magnetic anomalies of up to 180 nT. This layer is interpreted to include extrusive volcanic rocks related to the Cretaceous High Arctic Large Igneous Province (HALIP). Within the Amundsen Basin, three distinct crustal domains can be distinguished. Closest to the ridge is a 40-km-wide zone with a crustal thickness around 5 km interpreted as thinned continental crust. Five distinctive faulted basement blocks display high-amplitude reflections along their crests with velocities of 4.6 km s–1, representing the continuation of the magmatic rocks further upslope. Brozena et al. (2003) interpreted magnetic Chron C25 to be located in this zone but our data are not consistent with this being a seafloor spreading anomaly. In the adjacent crustal domain, heading basinward, the basement flattens and two layers with velocities of 5.2 and 6.8 km s–1 can be distinguished, where the upper and lower layer have a thickness of 1.5 and 2.0 km, respectively. The upper layer is interpreted as exhumed and highly serpentinized mantle while the lower layer may be less serpentinized mantle with some gabbroic intrusions. This may explain the high-amplitude reflections within the overlying sediments that are interpreted as sill intrusions. Continuing basinward, the last crustal domain represents 4-to 5-km-thick oceanic crust with a variable basement relief and velocities of 4.8 and 6.5 km s–1 at the top of oceanic layers 2 and 3, respectively. It is within this zone that the first true seafloor spreading anomaly Chron C24 is observed, which argues for a similar breakup age in the Eurasia Basin as in the Northeast Atlantic. On the other profile crossing the Lomonosov Ridge, a 60-km-wide intrusion into the lower crust is observed where velocities are increased to 6.9 km s–1. Gravity modelling supports the interpretation of magmatic underplating beneath the intrusion. Seismic data in this region show that the crust is overlain by a 2-km-thick series of high-amplitude reflections with a velocity of 4.8 km s–1 in a 30-km-wide zone where strong magnetic anomalies (>800 nT) are observed, suggesting a composition of basalt flows. This part of the Lomonosov Ridge appears therefore to have a HALIP-related magmatic overprint at all crustal levels.